# Class 12 RD Sharma Solutions- Chapter 5 Algebra of Matrices – Exercise 5.1 | Set 2

• Last Updated : 03 Jan, 2021

### Question 11: Find x, y and z so that A = B, where A= .

Solution:

As it is given that the matrices are equal, every element at a given index on the Left Hand Side (LHS) must be equal to the element at the same index on the Right Hand Side (RHS).

Hey! Looking for some great resources suitable for young ones? You've come to the right place. Check out our self-paced courses designed for students of grades I-XII

Start with topics like Python, HTML, ML, and learn to make some games and apps all with the help of our expertly designed content! So students worry no more, because GeeksforGeeks School is now here!

Thus,

a11 : x-2 = y ………….(eq.1)

a12 : z = 3    ………….(eq.2)

a13 : 2z = 6  ………….(eq.3)

a21 : 18z = 6y ……….(eq.4)

a22 : y+2 = x ………..(eq.5)

a23 : 6z = 2y …………(eq.6)

From (eq.2) and (eq.3),

=> z = 3

From (eq.4) and (eq.6),

=> y = 3z

=> y = 3(3)

=> y = 9

Substitute ( y=9 ) in (eq.1),

=> x-2 = 9

=>x = 11

Thus x=11, y=9 and z=3.

### Question 12: If , find x, y, z and w.

Solution:

As it is given that the matrices are equal, every element at a given index on the Left Hand Side (LHS) must be equal to the element at the same index on the Right Hand Side (RHS).

Thus,

a11 : x = 3      ………….(eq.1)

a12 : 3x-y = 2 ………….(eq.2)

a21 : 2x+z = 4 ………..(eq.3)

a22 : 3y-w = 7 ……….(eq.4)

From (eq.1) ,

=> x = 3

Substitute (x=3) in (eq.2),

=> 3(3)-y = 2

=> y = 3(3) – 2

=> y = 7

Substitute ( x=3 ) in (eq.3),

=> 2(3)+z = 4

=>z = 4-6

=>z = -2

Substitute (y=7) in (eq.4),

=>3(7) – w = 7

=>w = 21 – 7

=>w = 14

Thus x=3, y=7, z=-2 and w=14.

### Question 13: If , find x, y, z and w.

As it is given that the matrices are equal, every element at a given index on the Left Hand Side (LHS) must be equal to the element at the same index on the Right Hand Side (RHS).

Thus,

a11 : x-y = -1 ………….(eq.1)

a12 : z = 4     ………….(eq.2)

a21 : 2x-y = 0 ………..(eq.3)

a22 : w = 5 …………….(eq.4)

From (eq.2),

=> z = 4

And from (eq.4),

=> w = 5

Now, (eq.1) and (eq.3) form a system of equations comprising of variables x and y.

Thus, (eq.1) – (eq.2),

=> (x-2x) +(-y+y) = -1 – 0

=> -x = -1

=> x = 1

Substitute (x=1) in (eq.1),

=> 1-y = -1

=>y = 2

Thus, x=1, y=2, z=4 and w=5.

### Question 14: If . Obtain the values of a, b, c, x, y and z.

Solution:

As it is given that the matrices are equal, every element at a given index on the Left Hand Side (LHS) must be equal to the element at the same index on the Right Hand Side (RHS).

Thus,

a11 : x+3 = 0 ……………..(eq.1)

a12 : z+4 = 6    ………….(eq.2)

a13 : 2y-7 = 3y-2  ……..(eq.3)

a21 : 4x+6 = 2x ………….(eq.4)

a22 : a-1 = -3 ……………..(eq.5)

a23 : 0 = 2c+2 …………….(eq.6)

a31 : b-3 = 2b+4…………(eq.7)

a32 : 3b = -21………………(eq.8)

a33 : z+2c = 0………………(eq.9)

From (eq.1) and (eq.4),

=> x = -3

From (eq.2) ,

=> z+4 = 6

=> z = 2

From (eq.3),

=> 2y-7 = 3y-2

=> 3y-2y = -7+2

=> y = -5

From (eq.5),

=> a = -3+1

=> a = -2

From (eq.8),

=> 3b = -21

=> b = -7

Substitute (z=2) in (eq.9),

=> 2+ 2c = 0

=> c = -1

Thus, x=-3, y=-5, z=2, a=-2, b=-7 and c=-1.

### Question 15: If , find the value of (x+y).

Solution:

As it is given that the matrices are equal, every element at a given index on the Left Hand Side (LHS) must be equal to the element at the same index on the Right Hand Side (RHS).

Thus,

a11 : 2x+1 = x+3………..(eq.1)

a12 : 5x = 10 ………………(eq.2)

a21 : 0 = 0  …………………(eq.3)

a22 : y2+1 = 26 …………(eq.4)

From (eq.1) and (eq.2),

=> 2x+1 = x+3

=> x=2

From (eq.4),

=> y2+1 = 26

=> y2 = 25

=> y = ± 5

Thus if y = +5,

=> x+y = 7

And if y = -5,

=> x+y = -3

### Question 16: If , then find the values of x, y, z and w.

Solution:

As it is given that the matrices are equal, every element at a given index on the Left Hand Side (LHS) must be equal to the element at the same index on the Right Hand Side (RHS).

Thus,

a11 : xy = 8 ……………..(eq.1)

a12 : 4 = w ………………(eq.2)

a21 : z+6 = 0 …………..(eq.3)

a22 : x+y = 6 …………..(eq.4)

From (eq.2),

=> w = 4

And from (eq.3),

=> z = -6

Now, we can see that (eq.1) and (eq.4) form a system of equations comprising of variables x and y.

From (eq.1),

=> x = 8/y

Substitute (x=8/y) in (eq.4):

=> y + (8/y) = 6

=> y2 – 6y +8 = 0

Solving the above equation,

=> y2 – 4y – 2y + 8 = 0

=> y( y-4 ) -2( y-4 ) = 0

=> (y – 2)(y – 4) = 0

=> y = 2 or 4

Substitute in (eq.1):

=> when x=2, y=4 and when x=4, y=2.

Thus, (x,y) = (2,4) or (4,2) and z = -6 and w = 4.

### Question 17(i): Give an example of a row matrix which is also a column matrix.

Solution:

We know the order of a row matrix can be written as 1xn (1 row with n elements).

And similarly, the order of a column matrix is mx1.

So, a row matrix which is also a column matrix must be of the order (1×1).

As an example, we can take the matrix : ### Question 17(ii): Give an example of a diagonal matrix which is not scalar.

Solution:

In a diagonal matrix, only the diagonal elements possess non-zero values. Thus, for a nxn diagonal matrix, aii ≠ 0, for 1≤ i ≤ n.

And a scalar matrix is a diagonal matrix, such that all the diagonal elements are equal.

Thus, a matrix which is diagonal but not scalar is: ### Question 17(iii): Give an example of a triangular matrix.

Solution:

A triangular matrix is a square matrix, and it is filled in such a way that, either the triangle above the main-diagonal is non-zero (upper-triangular) or the triangle below the diagonal is non-zero (lower-triangular).

Thus, an example would be : ### Question 18: The sales figure of two car dealers during January 2013 showed that dealer A sold 5 deluxe, 3 premium and 4 standard cars, while dealer B sold 7 deluxe, 2 premium and 3 standard cars. Total sales over the month period of January- February revealed that dealer A sold 8 deluxe, 7 premium and 6 standard cars. In the same 2 month period, dealer B sold 10 deluxe, 5 premium and 7 standard cars. Write 2×3 matrices summarizing sales data for January and 2-month period for each dealer.

Solution:

The above data can be represented in the form of tables:

For January 2013,

For January to February,

Thus, the two matrices are : and ### A= and B = Solution:

As it is given that the matrices are equal, every element at a given index on the Left Hand Side (LHS) must be equal to the element at the same index on the Right Hand Side (RHS).

Thus,

a11 : 2x+1 = x+3 …………(eq.1)

a12 : 2y = y2+2 ……………(eq.2)

a21 : 0 = 0 …………………….(eq.3)

a22 : y2-5y = -6 …………..(eq.4)

From (eq.1),

=> 2x-x = 3-1

=> x=2

Taking (eq.2), it can be re-written as,

=> y2-2y+2 = 0

=> y = => y = -1 ± i ( No real solutions )

Taking (eq.4), it can be re-written as,

=> y2 – 5y +6 = 0

Solving the equation,

=> y2 – 2y – 3y +6 = 0

=> y( y-2 ) -3( y-2 ) = 0

=> ( y-2 )( y-3 ) = 0

=> y = 2 or 3

As values of y are inconsistent, we can say that the above matrices are not equal for any (x,y) pair.

### Question 20. Find the values of x and y if .

Solution:

As it is given that the matrices are equal, every element at a given index on the Left Hand Side (LHS) must be equal to the element at the same index on the Right Hand Side (RHS).

Thus,

a11 : x+10 = 3x+4 …………(eq.1)

a12 : y2+2y = 3   ……………(eq.2)

a21 : 0 = 0  ……………………..(eq.3)

a22 : y2-5y = -4   …………..(eq.4)

From (eq.1),

=> 2x = 6

=> x = 3

Taking (eq.2), it can be re-written as,

=> y2+2y-3 = 0

=> y2 + 3y -y -3 = 0

=> y( y+3 ) -1( y+3 ) = 0

=> ( y+3 )( y-1 ) = 0

=> y = -3 or 1

Taking (eq.3), it can be re-written as,

=> y2-5y+4 = 0

=> y2 -4y -y +4 =0

=> y( y-4 ) -1( y-4 ) = 0

=> ( y-4 )( y-1 ) = 0

=> y = 4 or 1

The value of y that can satisfy both (eq.2) and (eq.3) is 1.

=> y=1

Thus, x=3 and y=1.

### Question 21. Find the values of a and b if A = B , where A= , B= .

Solution:

As it is given that the matrices are equal, every element at a given index on the Left Hand Side (LHS) must be equal to the element at the same index on the Right Hand Side (RHS).

Thus,

a11 : a+4 = 2a+2 …………..(eq.1)

a12 : 3b = b2+2   …………..(eq.2)

a21 : 8 = 8  ……………………..(eq.3)

a22 : -6 = b2-5b   ………….(eq.4)

From (eq.1),

=> a = 2

Taking (eq.2), it can be re-written as,

=> b2-3b+2=0

=> b2 – 2b -b +2 = 0

=> b(b-2) -1(b-2) = 0

=> (b-2)(b-1) = 0

=> b=1 or 2

Taking (eq.4) it can be re-written as,

=> b2 -5b +6 = 0

=> b2 – 3b -2b + 6 = 0

=> b( b-3 ) -2( b-3 ) = 0

=> ( b-3 )( b-2 ) = 0

=> b = 2 or 3

Thus, b=2 can satisfy both (eq.2) and (eq.4).

=> b = 2

Thus, a=2 and b=2.

My Personal Notes arrow_drop_up